The Role of Governance in International Trade: Evidence from G20 Countries - Kiliç, Mustafa Canfer; Şeker, Ayberk (Bursa Uludağ Üniversitesi, 2025)
International trade volume has increased, highlighting various commercial risks with the acceleration of globalization in the late 20th century. Transparency, political stability, and a strong legal framework are crucial for investors in maintaining a secure trade environment. This study examines the impact of governance indicators on international trade. In this context, governance indicators such as accountability, rule of law, control of corruption, political stability, government effectiveness, and regulatory quality—established by the World Bank—are recognized as key determinants of international trade. Panel data analysis was conducted using data from G20 countries for the period 2002-2022 to test the effects of governance indicators on international trade. The findings reveal that control of corruption and accountability have the most significant positive impact on trade volume. Government effectiveness and regulatory quality also contribute positively to trade expansion. In contrast, political stability and rule of law were found to have no statistically significant effect on trade activity. In conclusion, reducing corruption, strengthening transparent governance mechanisms, and establishing an efficient institutional framework are critical for enhancing international trade volumes. Additionally, aligning trade policies with governance indicators is essential for ensuring long-term economic stability and global competitiveness.

20. yüzyılın sonlarında hızlanan küreselleşme ile birlikte uluslararası ticaret hacmi artmış ve ticari riskler öne çıkmıştır. Yatırımcılar için ticaret ortamının şeffaflığı, siyasi istikrarı ve hukuki altyapısı hayati önem taşımaktadır. Bu çalışma ile yönetişim göstergelerinin uluslararası ticaret üzerindeki etkisini incelemektedir. Bu bağlamda, Dünya Bankası tarafından belirlenen hesap verebilirlik, hukukun üstünlüğü, yolsuzluğun kontrolü, siyasi istikrar, kurumların etkinliği ve düzenlemelerin kalitesi gibi göstergeler, uluslararası ticaretin önemli belirleyicileri olarak kabul edilmektedir. G20 ülkelerinin 2002-2022 dönemi verileri kullanılarak panel veri analizi gerçekleştirilmiş ve yönetişim göstergelerinin uluslararası ticaret üzerindeki etkileri test edilmiştir. Elde edilen bulgular, yolsuzluğun kontrolü ve hesap verebilirliğin ticaret hacmi üzerinde önemli etkiye sahip olduğunu ortaya koymaktadır. Kurumların etkinliği ve düzenlemelerin kalitesi de ticaret hacmini olumlu yönde etkilemektedir. Buna karşın, siyasi istikrar ve hukukun üstünlüğü göstergelerinin istatistiki olarak anlamlı bir etkisi bulunmamıştır. Sonuç olarak, ülkelerin ticaret hacimlerini artırmak için yolsuzluğun azaltılması, şeffaf yönetim mekanizmalarının güçlendirilmesi ve etkili bir kurumsal yapının oluşturulması kritik öneme sahiptir. Bunun yanında, ticaret politikalarının yönetişim göstergeleriyle uyumlu hale getirilmesi, uzun vadeli ekonomik istikrar ve ticari rekabet gücünü arttırmak için gereklidir.
Uluslararası Ticarette Yönetişimin Rolü: G20 Ülkelerinden Kanıtlar
Keywords: International Trade (Other); Uluslararası Ticaret (Diğer)